The Politics of Power : The Political Economy of Rent-Seeking in Electric Utilities in the Philippines - Hasnain, Zahid; Matsuda, Yasuhiko (2012)
This paper takes advantage of unique intra-country variation in the Philippines power sector to examine under what conditions politicians have an incentive to "capture" an electric utility and use it for the purposes of rent-seeking. The authors hypothesize that the level of capture is determined by the incentives of, and the interactions between, local and national politicians, where the concepts of "local" and "national" are context specific. A local politician is defined as one whose electoral jurisdiction lies within the utility s catchment area; by contrast, a national politician is defined as one whose electoral jurisdiction includes two or more utility catchment areas. These jurisdictional differences imply different motivations for local and national politicians: because of "spillover" effects, local politicians have a greater incentive to use the utility for rent-seeking than a national politician as they capture only a portion of the political gains from utility performance improvements as some of the benefits of improved service will go to other electoral jurisdictions within the utility s catchment area. The authors posit that three variables impact the magnitude of these incentives of local and national politicians: (i) the local economic context, specifically the scale of rents that can be extracted from an electricity cooperative (ii) the degree of competitiveness of local politics; and (iii) the political salience of an electricity cooperative s catchment area for national politicians. The authors illustrate this framework through case studies of specific power utilities, and suggest some policy implications.